Maqasid shariah hifz mal in e-wallet application - Mastura Razali; Nurul’Ain Mohd; Nurhanisah Hadigunawan; Rafeah Saidon (Penerbit Universiti Kebangsaan Malaysia, 2021)
E-wallet is one of the most popular medium for digital transactions in Malaysia. With the wide variety of services provided by e-wallet companies, users find it convenient, faster and more efficient to do transactions. The application of e-wallet can be evaluated through the scope of hifz mal (preservation of property) of maqasid shariah so that it is always in compliance with shariah. The objective of this study is to discuss the application of hifz mal in e-wallet. The research methodology used is qualitative based on content analysis technique to obtain data. This study reviewed comprehensive articles and books relating to e-wallet, and views of Islamic scholars on the concept of hifz mal. In addition to the Central Bank of Malaysia (BNM), references were made to websites to obtain information on electronic money guidelines. Research findings show that using e-wallet as a medium for electronic transactions to purchase products or services is in line with the concept of hifz mal. Using money stored in e-wallet as medium of exchange in digital transactions is gaining wide public acceptance and does not involve elements of riba, gharar, gambling, and exploitation. In addition, e-wallet provides high security features and multiple maslahah that can facilitate people’s lives, which are in line with the principle of preserving property in maqasid shariah.